Efektivitas Pembelajaran Kooperatif Pelatihan Dasar Calon Pegawai Negeri Sipil di Balai Diklat Aparatur Kementerian Kelautan dan Perikanan - fuadi, afnanfuadi (Pusat Pendidikan dan Pelatihan Aparatur Perdagangan, 2021)
This study aimed to determine the effectiveness of cooperative learning methods in civil servant candidate training batch 7 at Apparatus Training Center, Ministry of Maritime Affairs and Fisheries This research were classroom action research with a quantitative approach. Data collection method used questionnaire, assignment sheet, interview and observation. This research conducted by comparing learning effectiveness in two different class namely experiment class that implement cooperative learning and control class that not implement cooperative learning. Learning effectiveness was assesed using two indicators namely activeness and learning result. Data analysis conducted by comparing learning result from experiment class and control class. The result of data processing shows that the average activeness score for the control class is 66.8% and the experimental class is 85.6%. The average learning result of the control class is 82.03 and the experimental class is 91.2. From these data, there is a percentage increase in the active score of participants from the control class compared to the experimental class 28.1% and the percentage increase in learning outcomes 11.2%. It can be conlused that cooperative learning method can increase the learning effectiveness of civil servant candidate training batch 7. Cooperative learning method can be used as alternative learning method at civil servant candidate training.